2015
DOI: 10.1038/nprot.2015.070
|View full text |Cite
|
Sign up to set email alerts
|

Intravital imaging of hair follicle regeneration in the mouse

Abstract: Hair follicles are mammalian skin organs that periodically and stereotypically regenerate from a small pool of stem cells. Hence, hair follicles are a widely studied model for stem cell biology and regeneration. This protocol describes the use of two-photon laser-scanning microscopy (TPLSM) to study hair regeneration within a living, uninjured mouse. TPLSM provides advantages over conventional approaches, including enabling time-resolved imaging of single hair follicle stem cells. Thus, it is possible to captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 40 publications
0
72
0
Order By: Relevance
“…These results suggest a simple model for stem cell fate without hierarchy or division asymmetry (23) (Fig. 2, B and C; figs.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…These results suggest a simple model for stem cell fate without hierarchy or division asymmetry (23) (Fig. 2, B and C; figs.…”
mentioning
confidence: 60%
“…We performed this multigenerational analysis in the ear epidermis and detected no mother-daughter bias in fate choice [supplementary theory (ST) S5] or in their lifetimes (Pearson correlation R = −0.11, P = 0.2). Second, we tested whether asymmetric fate divisions are the main mode of self-renewal, as widely suggested from static lineage tracing (10, 11, 15, 23). Asymmetric divisions should result in anticorrelated sister cell fates, but we found that sister cell fates were either independent (ear) or positively correlated (paw).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional confounding problem for analyzing epidermal homeostasis and lineage tracing in the laboratory mouse is their behavioral traits of scratching and grooming, which can inadvertently affect the outcome. At first glance, it may seem that the elegant live-imaging studies recently performed on mouse ear skin (Pineda et al, 2015; Rompolas, Mesa, & Greco, 2013) will offer a better avenue for tracing clonal behavior. Here, however is the issue of compressing the ear between glass plates in order to capture the image.…”
Section: Mammalian Epidermis Homeostasis and Stem Cellsmentioning
confidence: 99%
“…We are currently applying this technology to generate an in vitro optic cup for retinal tissue growth by spatial control of Wnt signaling to pattern the differentiation of hESC to neural retina and retinal pigment epithelium. [11,40] Moreover, the two photon excitation approach can also be combined with in vivo imaging [41] to become a promising means for investigation of developmental processes in vivo.…”
Section: Communicationmentioning
confidence: 99%